Investigation of the effect on the physical and mechanical properties of the dosage of additive in self-consolidating concrete - Esen, Yuksel; Orhan, Eyyup (Korean Society of Civil Engineers-Ksce, 2016)
The objective of this study was to investigate the effect of superplasticizer and mineral admixture contents on the properties of Self-Consolidating Concrete (SCC). Silica fume was used as a mineral admixture and polycarboxylate based third generation superplasticizer was used as a chemical admixture. In order to determine the optimum admixture dosages; trial mixes were prepared with varying admixture dosages. Nine concrete mixtures with different admixture dosages were prepared from trial mixes. Hardened concrete properties and self-compactability criteria of these series were determined and test results were compared between these SCC mixtures. It was observed that 10S1.3A (10% Silica Fume, 1.3% Superplasticizer) and 10S1.5A (10% Silica Fume, 1.5% Superplasticizer) mixtures show the best performance with regard to fresh and hardened concrete properties.
Keywords: self-consolidating concrete; superplasticizer; silica fume